Risk in Investing in Emerging Markets - Parashar, Nayan (2007)
An emerging market is defined as the capital market of a developing country. If a country's GNP per capita did not achieve the World Bank's threshold for a high-income country, then that country's market is considered as an emerging market. In the investment world, the continuing demand for higher return and lower risk have fuelled a recent surge of interest in investing in ÃÂemerging markets. BRIC countries are the fastest growing markets in the world and have attracted the investors attention only in the past few years. Strong macro-economic fundamentals, positive investment climate and sound business outlook have driven the bullish trend, which is currently being followed in these countries. This research, studies the risk of investing in emerging markets. It also looks into of the risk factors which affect the FDI inflow in these countries, and also determines the affect of the FDI determinants on the FDI inflows. Further the research compares the risk with rest of the world during the period 2002-2007. It concludes that it is not very risky to invest in BRIC countries though it is riskier than investing in non-emerging countries.